Pengembangan LKPD Menulis Pantun Berbasis Pedagogi Genre Berbantuan Kamus Rima Kata Online di Sekolah Dasar - Yuharjo Sipin; Abdul Muktadir; Bambang Parmadie (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
The purpose of this study was to describe the development, feasibility, and response, as well as to determine the effectiveness of LKPD Writing Pantun Based on Genre Pedagogy Assisted by Online Rima Kata Dictionary in Elementary Schools. This type of research is Research & Development (R & D), with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research sites are at SDIT Al-Ahsan and SDN 69 Seluma on February 21 – March 8, 2022. Based on the needs analysis, students and teachers need LKPD in learning to write pantun. The LKPD design is made by combining the LKPD structure format, genre pedagogical approach, and the rima kata dictionary media used. Design this LKPD using the Canva app. This LKPD is suitable for use with very high content validity in material and language aspects (1), and high media aspects (0.7), with medium inter-rater reliability in material aspects (40%), strong language aspects (70%), and weak media aspect (30%). The teacher's response to the use of the LKPD was very good, as was the response of the students (97.8%). This LKPD is effectively used and proven to improve student learning outcomes in writing pantun